Smart factory reference model for training on industry 4.0 / Ubaidullah Mohammad...[et al.] - Mohammad, Ubaidullah; Cheng, Yee Low; Abd Rahman, Ramhuzaini; Johar, Muhammad Akmal; Ching, Theng Koh; Roman, Dumitrescu; Martin, Rabe; Asmar, Laban; Kamaruddin, Susana (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Technological disruption and rising labour costs are impacting the future of manufacturing in Malaysia and its competitive position. Nevertheless, the understanding on smart manufacturing in the context of Industry 4.0 is still lacking in the academia and industry. Thus, this work describes the development of a smart factory reference model as a guide to upgrading an existing production system towards the vision of Industry 4.0 using readily available components. The reference model consists of (i) a principle solution describing the concept of a smart factory and (ii) a working prototype demonstrating the functionality of a smart factory. The smart factory prototype is a modular production system connected to a server accessible locally or through the internet and able to produce up to eight variants of a product. The SCADA software was used to interface various systems together and create the user interface. The prototype was evaluated using VDMA Industry 4.0 Toolbox. This work provides a way to integrate theory and practical Industry 4.0 applications into tertiary education curricula. It showcases the potential applications, benefits and proof of concept of new technologies for industry adoption.